Physical Activity in Schizophrenia is Higher in the First Episode than in Subsequent Ones - Walther, Sebastian; Stegmayer, Katharina; Horn, Helge; Razavi, Nadja; Müller, Thomas J.; Strik, Werner (Frontiers in Psychiatry, 2015)
Schizophrenia is frequently associated with abnormal motor behavior, particularly hypokinesia. The course of the illness tends to deteriorate in the first years. We aimed to assess gross motor activity in patients with a first episode (n = 33) and multiple episodes (n = 115) of schizophrenia spectrum disorders using wrist actigraphy. First episode patients were younger, had higher motor activity and reduced negative symptom severity. Covarying for age, chlorpromazine equivalents and negative symptoms, first episode patients still had higher motor activity. This was also true after excluding patients with schizophreniform disorder from the analyses. In first episode patients but not in patients with multiple episodes, motor activity was correlated with antipsychotic dosage. In conclusion, after controlling for variables related to disorder chronicity, patients with first episodes were still more active than patients with multiple episodes. Thus, reduced motor activity is a marker of deterioration in the course of schizophrenia spectrum disorders.